Longitudinal analysis of the effect of water hardness on atopic eczema: evidence for gene–environment interaction. (22nd December 2019) - Jabbar‐Lopez, Z.K.; Craven, J.; Logan, K.; Greenblatt, D.; Marrs, T.; Radulovic, S.; McLean, W.H.I.; Lack, G.; Strachan, D.P.; Perkin, M.R.; Peacock, J.L.; Flohr, C.
Summary: Background: Several studies have identified an association between water hardness and atopic eczema (AE); however, there is a paucity of longitudinal data in early life. Objectives: To examine whether water hardness is associated with an increased risk of AE and skin barrier dysfunction in infants and to assess effect modification by filaggrin (FLG) loss‐of‐function variants. Methods: We performed a longitudinal analysis of data from infants in the Enquiring About Tolerance (EAT) study, who were enrolled at 3 months and followed up until 36 months of age. Results: Of 1303 infants enrolled in the EAT study, 91·3% ( n = 1189) attended the final clinic visit and 94·0% ( n = 1225) of participants' families completed the 36‐month questionnaire. In total, 761 (58·4%) developed AE by 36 months. There was no overall association between exposure to harder (> 257 mg L −1 CaCO3 ) vs. softer (≤ 257 mg L −1 CaCO3 ) water: adjusted hazard ratio (HR) 1·07, 95% confidence interval (CI) 0·92–1·24. However, there was an increased incidence of AE in infants with FLG mutations exposed to hard water (adjusted HR 2·72, 95% CI 2·03–3·66), and statistically significant interactions between hard water plus FLG and both risk of AE (HR 1·80, 95% CI 1·17–2·78) and transepidermal water loss (0·0081 g m −2 h −1 per mg L −1 CaCO3, 95% CI 0·00028–0·016). Conclusions: There is evidence of an interaction between water hardness and FLG mutations in the development of infantile AE. Linked Comment:  Arents and Leonardi-Bee. Br J Dermatol 2020; 183:203–204 . Abstract : What's already known about this topic? Several cross‐sectional studies have found an association between domestic water hardness exposure and atopic eczema (AE) risk. Loss‐of‐function mutations in the skin barrier gene filaggrin ( FLG ) are the strongest genetic risk factor for AE. What does this study add? There was no overall association between AE risk and exposure to harder vs. softer domestic water in a large, well‐phenotyped cohort of infants living in England and Wales followed up at 3–36 months of age. However, infants with at least one FLG loss‐of‐function mutation exposed to harder water have a threefold increased risk of developing AE up to age 36 months compared with infants with wild‐type FLG exposed to softer water. Linked Comment:  Arents and Leonardi-Bee. Br J Dermatol 2020; 183:203–204 . Plain language summary available online